2006
DOI: 10.1159/000097790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Anthropometric and Upper Airway Anatomic Characteristics of Obese Patients with Obstructive Sleep Apnea Syndrome

Abstract: Background: Obese subjects are at increased risk of developing obstructive sleep apnea syndrome (OSAS). However, the individual role of local (i.e., upper airway-related) and general (clinical and whole-body anthropometric) characteristics in determining OSAS in obese patients is still controversial. Objectives: To contrast the clinical, anthropometric and upper airway anatomical features of obese subjects presenting or not presenting with OSAS. Methods: Thirty-seven obese (BMI ≧30 kg/m2) males with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 48 publications
3
44
1
5
Order By: Relevance
“…(2) A recent study involving magnetic resonance imaging of the upper airways to evaluate obese individuals with and without OSAHS showed that, in isolation, greater deposition of fat at this anatomical level is not a determining factor for the development of OSAHS. (8) Of special note is the fact that the excessive daytime sleepiness caused by OSAHS is correlated with traffic accidents, as is well documented in the Knorst et al study appearing in this issue. We pulmonologists are increasingly called upon to manage quality-of-life issues, whether through monitoring environmental pollution, attempting to improve aerobic performance, encouraging smoking cessation, or promoting workplace sanitation, and, by extension, reducing the damage and insults that such factors cause in the lives of our patients.…”
Section: Editorialmentioning
confidence: 73%
“…(2) A recent study involving magnetic resonance imaging of the upper airways to evaluate obese individuals with and without OSAHS showed that, in isolation, greater deposition of fat at this anatomical level is not a determining factor for the development of OSAHS. (8) Of special note is the fact that the excessive daytime sleepiness caused by OSAHS is correlated with traffic accidents, as is well documented in the Knorst et al study appearing in this issue. We pulmonologists are increasingly called upon to manage quality-of-life issues, whether through monitoring environmental pollution, attempting to improve aerobic performance, encouraging smoking cessation, or promoting workplace sanitation, and, by extension, reducing the damage and insults that such factors cause in the lives of our patients.…”
Section: Editorialmentioning
confidence: 73%
“…However, some studies have demonstrated that the relation between BMI and OSA is unclear. BMI is the traditional marker for obesity, but there has been disagreement about whether it is risk factor for OSA [6,14,17,20]. BMI was increased especially in females with OSA, but it was not correlated with AHI in polysomnography [17].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in a group of 18 OSAS with higher BMI and larger neck circumference than the 11 controls included in the study, Hora et al found in awake patients using MRI that the transversal (lateral) dimension of the airway at the retroglossal level was an independent predictor of OSAs, and this lateral narrowing of the airway was not associated with increased fat pad thickness. 11 The authors conclude that the narrowing of the lateral airway is due to parapharyngeal muscular hypertrophy not the accumulation of fat. This conclusion agrees with the findings of Ciscar et al, who found in obese subjects that the parapharyngeal fat increase was not related to OSAS.…”
Section: Introductionmentioning
confidence: 96%